Characterization of Plasma Sprayed Hydroxyapatite-glass Composite Coatings onto Titatium Alloy Substrate - (:unkn) unknown (SCIENCE PRESS BEIJING, 2012)
Hydroxyapatite (HA) is one of the most promising biomaterials. HA-composite materials' are produced, because of the known mechanical weakness of HA. In this study, composite coatings were coated onto titanium alloy (substrate). To enhance the bonding strength between hydroxyapatite (HA-Glass) composite coatings and titanium alloy substrate, HA(5% and 10% rates Glass were added) composite coatings with and without bonding coatings (60% Al2O3- 40% TiO2) have been fabricated via plasma spraying. After coating, bonding strength evaluation and scanning electron microscopy (SEM) were carried out to characterize the composite coatings. The results obtained showed that the addition of bonding coatings (60% Al2O3- 40% TiO2) to HA-Glass composite coatings improved the bonding strength of the coating significantly.
Keywords: Hydroxyapatite (HA); plasma spraying; HA-Glass composite coatings; bonding strength; MECHANICAL-PROPERTIES; BHA